Needs Analysis: Project Based Learning and Digital Transformation of the Merdeka Curriculum IPA Terpadu Learning - Iman Nasrulloh; Rivan Syahrul Falah; Ihpad Maulana (Postgraduate, University of Mataram, 2025)
This study aims to analyze gaps and provide recommendations in project-based learning and digital transformation of the Merdeka Curriculum in integrated science learning. The research method uses a mixed methods approach. Qualitative data analysis was conducted by reducing data, presenting data, and drawing conclusions based on the results of interviews and observations. Quantitative data were obtained from questionnaires. The results showed that: 1) the gap that emerged was still in the form of student activity levels; 2) teachers' skills in creating learning websites needed to be improved; 3) digital learning had been implemented inside and outside the classroom; 4) teachers had basic computer skills; 5) teachers actively participate in teacher professional development; 6) obstacles in the implementation of the independent curriculum include student interests and talents; 7) providing support for teachers to participate in professional development; 8) teachers as facilitators; 9) the allocation of learning time for each meeting must be more than 2 hours of lessons; 10) limitations of equipment and materials for science practicum learning. Project-based learning and digital transformation need to pay attention to increasing student activity, learning web training, adding learning time allocation, availability of equipment and materials, and professional development.